Catmon road and drainage construction project - Phase 2 - Omaña, Terteen Gail B. (Animo Repository, 2023)
The PBSP Luzon Regional Operations is currently implementing the Strategic Private Sector Partnerships for Urban Poverty Reduction Program or STEP-UP which is an expansion of the NCR Area Resource Management This will be implemented in 23 urban poor communities in 8 cities to improve the quality of life of 5,823 households. This will be achieved through the implementation of 4 major components: a) Partnership Building; b) Revolving Fund for Livelihood and House Upgrading; c) Community Infrastructures and, d) Risk Reduction and Management. One of the priority areas, Malabon City has a total population of 336,516 or 74,137 households and growing at a rate of 1.92 percent As of 1996, there are a total of 22,094 informal family settlers. Among these settlers, 1000 reside in the 3 identified communities for the STEP-UP program. These are FLOVIHOMES 1 and 2, Dionisio Homeowners Association and 5 Catmon HOAs. They have acquired the land through the government's Community Mortgage Program. In Barangay Catmon, the program adopted 5 different HOAs with a total of 661 households. Currently, four (4) HOAs completed their CMP take out. These are Peoples Coalition Housing Rights HOA (PCHR), Samahan ng Pagkakaisa ng Dumpsite Catmon HOA (SAPADACA), Samahan ng Maralita ng Catmon HOA (SMC), and Kaunlaran ng Samahang Hernandez Catmon HOA (KSHC). However, the Samahan Tungo sa Kaunlaran ng Komunidad HOA (STKKC) is still in the Purchase Commitment Line stage (PCL) and is expected to complete its land acquisition year. Based on the interviews with the residents, income ranging from P5,000-P9,000/month is derived from scavenging of wastes, construction, and sewing. This is below Metro Manila's poverty threshold of P18,000 per month. Last fiscal year, PBSP approved Phase 1 of the Road and Drainage project covering 260 households of two (2) HOAs in Catmon (PCHR and SAPADACA). The project was completed last March 2005 covering the said HOAs and additional 47 households from neighboring community. Moreover, they were able to realize savings that was used to construct additional 125 linear meters as the main drainage of the four (4) HOAs except SMC HOA. It was completed last July 2005. Currently, PCHR HOA is implementing its electrification project in Barangay Catmon together with MERALCO and the LGU. The adjacent partner HOAs are assisting them in the implementation since they are targeting 298 households to be energized this month. Although the phase 1 project only covered two (2) associations, the three (3) associations still provided labor counterpart. The five (5) HOAs mobilized 1,926 volunteers who rendered a total of 15, 412 hours or P385,200.00 worth of labor. The project provided employment to sixteen (16) individuals for six (6) months with an average income of P 4,436.00 per month. The construction of the phase 2 will contribute full completion of the entire road network. Hence, there is a need to construct the remaining road and drainage that will provide systematic water flow in all 5 associations.